It Takes Three to Tango: Exploring the Interplay among Training Intensity, Job Autonomy, and Supervisor Support in Predicting Knowledge Sharing - Buch, Robert; Dysvik, Anders; Kuvaas, Bård; Nerstad, Christina G. L. (Human Resource Management, 2015)
This study explored whether the relationship between perceived training intensity and knowledge sharing is prone to combined moderating influences. We operationalized perceived training intensity as a challenge stressor, in accordance with the challenge‐hindrance framework of work stressors. The results of a study of 129 employees from three Norwegian service industries revealed a positive relationship between perceived training intensity and supervisor‐rated knowledge sharing for employees reporting high levels of perceived job autonomy and high levels of perceived supervisor support. In contrast, we found a negative relationship between perceived training intensity and supervisor‐rated knowledge sharing for employees reporting high levels of perceived job autonomy and low levels of perceived supervisor support. These findings suggest that supervisors are of vital importance in facilitating knowledge sharing among employees in settings where developmental challenges are prevalent and perceptions of job autonomy are high. Implications for future research and practice are also discussed. © 2014 Wiley Periodicals, Inc.